Gaya Kepemimpinan Demokratis Di Sekretariat Dprd Kota Surabaya - Aqni Solicha, Putri Irfa'; Lestari, Yuni (Jurnal Inovasi Administrasi Negara Terapan (Inovant), 2023)
This research discusses the democratic leadership style in the Meeting and Legislation Section of the Surabaya Legislative Council Secretariat. The leader appointed in this research is Mr. Suharto as the head of the Meeting and Legislation Section. It was found that the leader is a leader who is respected and respected by his subordinates. Leaders who give instructions to their subordinates. Always invites them to participate In leading he often includes his subordinates in submitting suggestions and opinions. The purpose of this research is to describe the leadership style at the Surabaya City DPRD Secretariat. The method used is descriptive qualitative method, namely decisions made together, appreciating the potential of subordinates, listening to criticism and suggestions from subordinates, cooperating with subordinates. With data collection techniques through interviews, observation, and documentation. Leaders always give a positive response to proposed ideas. In addition, the provision of rewards such as bonuses, meals together. appreciate the potential of each team member by giving attention and recognizing the contributions made. The attitude of listening to ideas and input from subordinates shows that this leader is able to appreciate diverse perspectives and considers each voice as an added value to the group.Leaders are open to criticism and praise given to them. encourage subordinates to provide constructive suggestions in the form of criticism and suggestions that help in improving their performance. leaders strengthen cooperation by valuing contributions. Leaders recognize the importance of collaboration in achieving common goals. An open and fair attitude in giving feedback strengthens trust among team members.Leaders communicate well with subordinates. They actively discuss every problem. Leaders create a comfortable and open working environment. Leaders adopt an approach that gives trust to their subordinates.   Keywords: Leadership Style, Democratic Leadership, Head of Section